Viscous properties of new mould flux based on aluminate system with CeO2 for continuous casting of RE alloyed heat resistant steel - 亓捷 刘承军 李春龙 姜茂发 (Journal of rare earths, 2016)
The conventional mould fluxes can not be applied to the continuous casting of RE alloyed heat resistant steel, because severe slag-metal interface reactions occur generally in the mold. To restrain the interface reaction and improve conditions for continuous casting, a new mould flux based on aluminate system was devised. The viscous properties were investigated. Scanning electron microscopy and X-ray diffraction were applied to detect and characterize the crystalline phases in the continuous cooling process. The results showed that appropriate addition of CeO_2 could avoid the precipitation of CaO and decrease the viscosity of the mould flux. Increasing the mass ratio of CaO /Al_2O_3, especially to a value exceeding 1, could worsen the stability of the mould flux. With a content of less than 14 wt.%, Li_2O could reduce the viscosity and breaking temperature, but its effect could be weakened for the promoted precipitation of LiAlO_2. To obtain a mould flux with stable viscous properties, such as viscosity and breaking temperature, appropriate contents of CeO_2 and Li_2O should be controlled to around 10 wt.% and 14 wt.%, while the mass ratio of CaO /Al_2O_3 should not be more than 1.